1985
DOI: 10.1007/bf00427330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple pretreatment with apomorphine and amphetamine on amphetamine-induced locomotor activity and its inhibition by apomorphine

Abstract: Mice were given a saline preinjection and habituation to the testing environment followed by injection of amphetamine (0.675-5.0 mg/kg IP) and apomorphine (AP, 15-80 micrograms/kg SC) 15 min later. AP produced a dose-dependent inhibition of the amphetamine-induced locomotor activity. A dose of 40 micrograms/kg AP increased approximately threefold the amphetamine dose required to induce the same increase in activity. Repeated administration of AP (30 mg/kg IP once daily for 14 days) resulted in an enhanced resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Again, these e¤ects were consistent with the well known actions of d-amphetamine and apomorphine as established in numerous earlier studies (e.g. Ri¤ee and Wilcox 1985;Geyer et al 1987;Mazurski and Beninger 1988;Druhan et al 1993;Ott and Mandel 1995). The overall similarity between the basic dose-e¤ect relations obtained with PPI and activity measures in this study and results reported elsewhere underscores the reliability of the procedures and measures employed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Again, these e¤ects were consistent with the well known actions of d-amphetamine and apomorphine as established in numerous earlier studies (e.g. Ri¤ee and Wilcox 1985;Geyer et al 1987;Mazurski and Beninger 1988;Druhan et al 1993;Ott and Mandel 1995). The overall similarity between the basic dose-e¤ect relations obtained with PPI and activity measures in this study and results reported elsewhere underscores the reliability of the procedures and measures employed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Also, repeated administration of APO or AMP produces an increased stereotypy and motor response to AMP (Segal and Mandell 1974;Wilcox et al 1980;Riffee and Wilcox 1985). Similar to the results in the present study, the regulation of presynaptic activity by DA agonists is not impaired following chronic APO, and there are no corresponding changes in the maximal number or affinity of 3H-spiroperidol binding sites (Riffee et al 1982;Riffee and Wilcox 1985).…”
Section: Discussionsupporting
confidence: 79%
“…Acute or repeated stress selectively activates mesocortical DA turnover (Fadda et al 1978;Herman et al 1982), increases the stereotypy response to AMP (Antelman and Chiodo 1983) and APO (Csernansky et al 1984), and the locomotor responses to AMP and APO (Herman et al 1984). Also, repeated administration of APO or AMP produces an increased stereotypy and motor response to AMP (Segal and Mandell 1974;Wilcox et al 1980;Riffee and Wilcox 1985). Similar to the results in the present study, the regulation of presynaptic activity by DA agonists is not impaired following chronic APO, and there are no corresponding changes in the maximal number or affinity of 3H-spiroperidol binding sites (Riffee et al 1982;Riffee and Wilcox 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphetamine becomes available in the brain within minutes following an i.p. injection (Riffee and Wilcox, 1985) and, therefore, we chose a time point of 2 h after amphetamine injection to test for changes in the AMPAR/NMDAR ratio. At 2 h following amphetamine injections, we prepared acute slices from those animals with a locomotor response greater than 120 ambulation counts/hour, (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%